Is human health sufficiently protected from chemicals discharged with treated ballast water from vessels worldwide? – A decadal perspective and risk assessment. (November 2019) - Dock, Annette; Linders, Jan; David, Matej; Gollasch, Stephan; David, Jan
Abstract: Ballast water managements systems (BWMS) installed on vessels may use active substances to inactivate organisms. This paper provides new insights in the global issue of noxious disinfection by-products (DBP) discharge with ballast water, and the related risk assessment for human health. The GESAMP ballast water working group plays a role in the certification process of BWMS that make use of active substances evaluating potential negative effects. We analyzed all BWMS that passed GESAMP final approval over a decade until 2017 providing an overview of chemicals in the discharged ballast water generated by BWMS. We used these data to calculate the chemical load humans may be exposed to for two different commercial ports (Koper, Slovenia and Hamburg, Germany). None of the chemicals in this study reached levels of concern that would indicate a risk for humans after exposure to chemicals present in the discharged ballast water. Nevertheless, although this exposure only adds to a lesser degree to the overall exposure to disinfection by-products, some chemicals, such as tribromomethane, have carcinogenic properties. In case studies we show which chemicals have the largest contribution to the aggregated exposure of humans. We note that tribromomethane, despite its low bio-concentration factor (BCF), may accumulate in fat, when fish are continuously exposed to DBPs during low-level chlorination. Since this figure would give a higher value for the internal dose for tribromomethane from seafood consumption than the current BCF in the GISIS database, the calculated value may underestimate the contribution of tribromomethane, and possibly also other DBPs. Highlights: Water discharges of 42 ballast water management systems were studied. Active substances, disinfection by-products and neutralizers were analyzed. No unacceptable human health risk of treated ballast water was noted. Revise the current BCF value for tribromomethane. Take permeation coefficient, Kp, into account for skin absorption when available.